Effects of Supplementation with the Standardized Extract of Saffron (affron®) on the Kynurenine Pathway and Melatonin Synthesis in Rats - Mario De la Fuente Muñoz; Marta Román-Carmena; Sara Amor; Ángel Luís García-Villalón; Alberto E. Espinel; Daniel González-Hedström; Miriam Granado García (MDPI AG, 2023)
Melatonin is a hormone that regulates sleep-wake cycles and is mainly synthesized in the pineal gland from tryptophan after its conversion into serotonin. Under normal conditions, less than 5% of tryptophan is reserved for the synthesis of serotonin and melatonin. The remaining 95% is metabolized in the liver through the kynurenine pathway. Increased levels of proinflammatory cytokines and cortisol increase the metabolism of tryptophan through the kynurenine pathway and reduce its availability for the synthesis of melatonin and serotonin, which may cause alterations in mood and sleep. The standardized saffron extract (affron®) has shown beneficial effects on mood and sleep disorders in humans, but the underlying mechanisms are not well understood. Thus, the aim of this work was to study the effects of affron® supplementation on the kynurenine pathway and the synthesis of melatonin in rats. For this purpose, adult male Wistar rats were supplemented for 7 days with 150 mg/kg of affron® or vehicle (2 mL/kg water) administered by gavage one hour before sleep. Affron® supplementation reduced body weight gain and increased the circulating levels of melatonin, testosterone, and c-HDL. Moreover, animals supplemented with affron® showed decreased serum levels of kynurenine, ET-1, and c-LDL. In the pineal gland, affron® reduced Il-6 expression and increased the expression of Aanat, the key enzyme for melatonin synthesis. In the liver, affron® administration decreased the mRNA levels of the enzymes of the kynurenine pathway Ido-2, Tod-2, and Aadat, as well as the gene expression of Il-1β and Tnf-α. Finally, rats treated with affron® showed increased mRNA levels of the antioxidant enzymes Ho-1, Sod-1, Gsr, and Gpx-3, both in the liver and in the pineal gland. In conclusion, affron® supplementation reduces kynurenine levels and promotes melatonin synthesis in rats, possibly through its antioxidant and anti-inflammatory effects, making this extract a possible alternative for the treatment and/or prevention of mood and sleep disorders.